Effect of emotional priming on eating willingness of women with restrictive diet - Lv, Yuchen; Chen, Ying; Xiong, Weirui (Frontiers in Psychology, 2024)
Background There is controversy regarding whether negative or positive emotions have a greater impact on the eating behavior of restrictive dieters. Moreover, it is unclear whether unconscious emotional processing can predict the eating behavior of restrictive dieters. This study investigated the effects of conscious and unconscious emotional processing on the dietary behavior of women with restrictive diet. Methods Female student participants (N = 600) completed the Dutch Eating Behavior Questionnaire to screen 60 each of successful, unsuccessful restrictive and unrestricted eaters. They were randomly and equally divided into two groups for supra-threshold and subliminal emotional priming and carried out a behavioral task to index eating intentions. Results The restrictive dieters increase their willingness to eat when they are in a positive mood, even if they are not consciously aware of their happiness. Furthermore, the unsuccessful restrictive dieters are more intense. Conclusion This study presents empirical evidence on the impact of positive emotions on the eating intention of restrictive dieters and the cognitive characteristics of unsuccessful restrictive dieters. Additionally, it offers guidance for unsuccessful restrictive dieters to personalize their treatment goals.